Wiskott-Aldrich Syndrome Protein: Roles in Signal Transduction in T Cells - Ngoenkam, Jatuporn; Paensuwan, Pussadee; Wipa, Piyamaporn; Schamel, Wolfgang W. A.; Pongcharoen, Sutatip (Frontiers in Cell and Developmental Biology, 2021)
Signal transduction regulates the proper function of T cells in an immune response. Upon binding to its specific ligand associated with major histocompatibility complex (MHC) molecules on an antigen presenting cell, the T cell receptor (TCR) initiates intracellular signalling that leads to extensive actin polymerization. Wiskott-Aldrich syndrome protein (WASp) is one of the actin nucleation factors that is recruited to TCR microclusters, where it is activated and regulates actin network formation. Here we highlight the research that has focused on WASp-deficient T cells from both human and mice in TCR-mediated signal transduction. We discuss the role of WASp in proximal TCR signaling as well as in the Ras/Rac-MAPK (mitogen-activated protein kinase), PKC (protein kinase C) and Ca2+-mediated signalling pathways.